A book mall in New Clark City - Uy, Wyllden Oliver T. (College of Architecture, University of the Philippines Diliman, 2019)
The thesis project entitled A book mall in New Clark City focused on determining the architectural interventions that will address the issue of overcrowding in the NCR, through integrating the creation of a community-inclusive space with New Clark City as the target location -- it was seen that New Clark City by itself was an answer to the overcrowding issue of Metro Manila by dispersing national development from the capital to other regions of the country. The thesis then advances the idea of using a unique concept of a book mall as a catalyst for commercial and social development in the area. The study examined the various factors that will enable or serve as barriers in the realization of the concept. The original vision of the thesis project is simply a book mall, one that is a hybrid between a public library and a bookstore. along with spaces dedicated for book-related activities such as book signing, book launching, book trades, book fairs. After doing research and making the initial architectural programming of spaces, it was found out that even non-literary activities are able to complement the reading activities and create a more holistic experience for the users, and so these were incorporated to the overall program. Finally, some elements regarding Green Building design were also added after the design translation was presented, and additional drawings were included to further comply to the green and sustainable character of New Clark City.